Efecto de la distancia al acceso de trasporte masivo Megabús sobre el valor de la propiedad en la zona subcentro cuba (Pereira) (2011)
This paper examines what the effect of the distance between access to mass transportation system "Megabus" on the value of the property in the center sub Cuba (Pereira), the methodology used in this work is the hedonic price is estimated a model that explains the variations in price depending on the attributes of housing, including the distance to the massive access buses. The results show that for every meter away property that the price decreases by $ 42. Now, if the property is commercial price increases $ 38,216. For Cuba, the center sub zone accessibility variable "distance" affects the price of the property.